Protótipo de automação de baixo custo para pulverizadores de barra na aplicação de defensivos agrícolas - Alves, Fernando de Lima (2016)
The application of pesticides has contributed to increase agricultural yield in Brazil, consequently, electronic controllers have been used in modern agriculture. Thus, this study aimed at developing an automation embedded prototype to change to sprinklers with an embedded electronic device in order to reduce the risks to the operator's health since there is no hand contact with the nozzles. It was developed a complete prototype with three sets of application that was controlled in an independent way for each type of nozzle sets. The applications were carried out on water-sensitive paper labels, whose working pressure nozzles were calibrated at 4.1 bar to check the equipment quality on application as well as the volumetric median diameter - VMD, numeric median diameter NMD, drop density, cover percentage and drop volume. The results from flow tests were based on catalog data provided by the tested nozzle manufacturer. The prototype was robust and efficient for practical use and it was also possible to carry out nozzles changing in a quick way and without hand-operator contact with the studied nozzles